IMPLEMENTASI MODEL PROJECT-BASED LEARNING (PJBL) BERBASIS SOCIO-SCIENTIFIC UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS V SD ISLAM NURUS SYAMSI - M. Sulthan Bayu S; Ludfi Arya Wardana; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve scientific literacy in science learning by using a socio-scientific learning model based on projects on environmental issues that threaten the lives of fifth grade students. The study was conducted using the Kemmis & McTaggart (1988) classroom action research (CAR) method consisting of 4 stages, namely planning (plan), action (act), observation (observe), and reflection (reflect). The subjects of this study were 20 fifth grade students of SD Islam Nurus Syamsi consisting of 12 male students and 8 female students. This study was conducted in 2 cycles and each cycle had 1 meeting. The criteria for passing science literacy skills with a score of 33.3% - 66.6% are in the medium category and for scores above 66.6-100% are in the high category. The results of this study indicate a change in the results of improving science literacy skills. In cycle II, the results of science literacy skills increased from the previous cycle, increasing in cycle II, namely with an average of 80.25, which is included in the good category.